Effect of Kapalbhati on Blood Pressure in Naive - Jha, Santosh Kumar; Goit, Rajesh Kumar; Upadhyay-Dhungel, Kshitiz (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: Kapalbhati is among one of the cleansing act (shatkarma) in yogic philosophy. It is highly recommended for those who have to do great deal of study and need a clean, clear mind. This study was conducted among medical students at Nepalgunj medical college, Nepalgunj, Nepal. Material and Methods: This analytical study was conducted among 100 medical students of Nepalgunj Medical College, Nepalgunj, Nepal who gave consent and performed Kapalbhati correctly were included in the study. SBP and DBP were the cardiac parameters taken. Those parameters were taken before, immediately, after 1 minute, 2 minutes and 3 minutes of Pranayama. The data were entered in SPSS and Statistical analysis was done using version 23. Results: As in usual exercises, SBP and DBP increases significantly immediately after Kapalbhati session when compared with the value before exercises. The basal (pre-Kapalbhati) mean SBP and DBP were 125.76 ± 7.36 and 82.92 ± 5.75 which increases up to 143.60 ± 11.18 and 90.33 ± 7.90 respectively immediately after exercises and fall after 3 minutes of exercises value being 127.05 ± 10.93 and 81.38 ± 5.38 respectively. Conclusion: There is significant rise between Pre-value and post-value (immediate) of all parameters and significant fall of all parameters if compared between post-value and after 3 minute. Janaki Medical College Journal of Medical Sciences (2017) Vol. 5(1): 16-21